P-011 Treatment of intracranial aneurysms: does size matter?. (4th July 2012) - Baldwin, C; Turk, A; Chaudry, I; Turner, R
Abstract : Object: Retrospective analysis and improved early detection of both ruptured and incidentally discovered very small cerebral aneurysms (<4 mm) has lead to increased concern over their management. Previous studies have reported lower incidence of spontaneous rupture and increased risk during surgical interventions. Development of smaller and softer finishing coils likley allow for safer treatment of smaller aneurysms than historically reported. The authors of the current study describe the presentation and procedural outcomes of both ruptured and incidental very small (<4 mm) and small (4–7 mm) cerebral aneurysms in contrast to larger, less controversial, intracranial aneurysms (>7 mm). Methods: The authors retrospectively evaluated 347 patients harboring 375 aneurysms treated for ruptured or incidentally discovered intracranial aneurysms between the dates September 2007 and May 2011. Patients harboring pseudoaneurysms or untreated incidental or ruptured aneurysms were excluded from the study. Data on rupture status at presentation, measured dimensions at surgical intervention, procedural complications and challenges, and length of patient hospitalization was collected. Results: Patients, 264 (76.08%) female and 83 (23.92%) male with a mean age of 55.37, presented w. 87 (23.20%) as very small cerebral aneurysms (<4 mm) and 147 (39.20%) as small cerebral aneurysms (4–7 mm). Of the VSCA 25 (28.73%) were unruptured and 58 (66.7%) were ruptured. Small cerebral aneurysms had a presentation of 94 (63.9%) ruptured and 53 (36.01%) unruptured. Larger cerebral aneurysms made up 37.6% of treated aneurysms. 74 (52%) of which presented as ruptured and 47% (n=67) unruptured. Abstract P-0011 table 1 details differences in procedural difficulty or complications were not significantly different among size groupings. Specifically, intraprocedural ruptures did not occur at a significantly different rate in very small cerebral aneurysms (3.6%) when compared to larger (>4 mm) intracranial aneurysms (2.7%). Conclusion: Although controversy still surrounds the treatment of very small cerebral aneurysms, the current study has shown that these aneurysms compose a significant proportion of both incidental and ruptured aneurysms presenting to the Medical University of South Carolina. Comparative complications rates between larger and very small cerebral aneurysms of the same rupture status suggest that surgical intervention is feasible and should be considered in their treatment plan. Competing interests: C Baldwin: None. A Turk: Stryker, Penumbra, Siemens, Microvention, eV3, Pulsar Vascular, NFocus, Lazarus Effect. I Chaudry: None. R Turner: Microvention, Codman, Penumbra, ev3.